Lisyun qng geografia - Vargas, Hil Petersen Miranda 1992-; Tolentino, Roland B.; University of the Philippines. College of Mass Communication (Quezon City University of the Philippines Diliman, 2014)
"Lisyun qng Geografia (Geography Lessons) tells the story of Tib Apostol who, before leaving his hometown for good, finds himself looking for his best friend, Tric Torres, back in high school. Guided by a map his bestfriend made for him, Tib attempts to visit each place around Pampanga to retrace the memories of his friendship with Tric. The film attempts to deconstruct the prevailing hetero-norm surrounding the development of the characters' personal narratives set against the backdrop of a common context. The "lesson" (lisyun) of geography (geografia) is the revelation of the landscape of "memory". The act of remembering is both portrayed and criticized in the film. Memory is susceptible to change, as is also the case with Pamapanga, which bears the "map" of the discourse. With an alienating and unidentifiable context, the personal narrative of the "homosexual" becomes an identity that can either be remembered or forgotten. Through the exploration of the dialectic of the personal and the social, the filmmaker aims to evaluate another essential lesson - love, however elusive, is never lost, only forgotten, and we can only hope the same for our "selves"."
Vita.
Undergraduate thesis
Keywords: Lisyun qng geografia (Short film) -- Philippines; Gay men -- Identity; Social norms; Love; Short films -- Philippines